Effects of R&D expenditure on employment growth : a dynamic panel analysis. - Said, Rusmawati; Samsi, Aznita; Wan Ngah, Wan Azman Saini (2012)

(untitled)
This paper estimates the effects of research and development (R&D) expenditure on the employment growth in Malaysian manufacturing sector during the period 2000 to 2008. Theoretical literatures devote the link between R&D and employment structure tends to suggest technological change has positive effects on job. Using dynamic panel GMM system estimation and 3 digit industry levels from manufacturing survey over the period 2000 to 2008, this paper find there is negative and significant relationship between R&D expenditure and employment growth. This is true when we consider with the second lag of the variable. Employment growth in Malaysian labour market however still favour to labour oriented and the absorption of the new technology is considered low.